The Presence of Methanol In Alcoholic Beverages Analyzed Using Qualitative Method - Navianti, Diah; Tarmizi, Muhammad Ihsan; Holifah, Sinta Nur (POLTEKKES KEMENKES YOGYAKARTA, 2018)
An alcoholic beverage contains ethyl alcohol or ethanol (C2H5OH)that is produced from fermentation or distillation of sugars. In many cases, either producers or consumers add ethanol with denaturated alcohol containing methanol (CH3OH) as an additive. Methanol can cause blindness and induce comas, and it is deadly in high doses. This study aimed at investigating the presence of methanol or methyl alcohol in alcoholic beverages sold in Palembang, Indonesia. Seventeen samples collected from small shops and supermarkets were taken by accidental sampling. A chromotropic acid method was used to examine the presence of methanol. The results showed that there were 18% of the samples was positive, and 82% was negative. Based on alcohol content, the research showed that all (100%) samples of group A were negative; 33% of group B was positive, and 33% of group C was positive. The study indicated that methanol was still present in alcoholic drinks sold in markets. The government should inform the society that denatured alcohol contains methanol and, therefore, should not be feasible to consume.